Five-year incidence of age-related macular degeneration: the Beijing Eye Study - You, Qisheng; Jonas, Jost B. (Ophthalmology, 2012)
Purpose: To examine the incidence of age-related macular degeneration (AMD) and its associated factors in an adult Chinese population. Design: Population-based study. Participants: The Beijing Eye Study, which included 4439 subjects (age ≥40 years) in 2001, was repeated in 2006 with 3251 (73.2%) subjects participating. Methods: Fundus photographs were graded using the International Age-related Maculopathy Epidemiological Study Group grading system. Main Outcome Measures Incidence of AMD. Results: Gradable slides were available on 3049 (93.9%) subjects who participated in the survey of 2001 and again in 2006. The incidence of early, late, and neovascular AMD per eye was 2.6% (95% confidence interval [CI], 2.2-3.0), 0.1% (95% CI, 0.00-0.2), and 0.1% (95% CI, 0.00-0.2), respectively. The incidence of early, late, and neovascular AMD per person was 4.2±0.4% (95% CI, 3.5-5.0), 0.1±0.1% (95% CI, 0.0-0.2), and 0.1±0.1% (95% CI, 0.0-0.2), respectively. By multivariate analysis, incident early AMD was associated significantly with greater age at baseline (P = 0.01; odds ratio [OR], 1.03; 95% CI, 1.01-1.06), smaller optic disc size (P = 0.007; OR, 0.50; 95% CI, 0.30-0.83), smaller scleral spur distance (P = 0.04; OR, 0.59; 95% CI, 0.36-0.98), and hyperopic refractive error (P = 0.057; OR, 1.15; 95% CI, 1.00-1.33), with the latter being significant only marginally. It was not associated with the systemic parameters of gender, body height, body mass index, region of habitation, level of education, profession, smoking, arterial blood pressure, diabetes mellitus, fasting blood concentrations of glucose, triglycerides, high-density or low-density lipoproteins; or the ocular parameters of intraocular pressure, retinal arterial and vein diameters, retinal microvascular abnormalities, amount of nuclear cataract, cortical cataract or subcapsular cataract, pseudophakia, glaucoma, nonglaucomatous optic neuropathy, retinal vein occlusions, size of the beta zone of parapapillary atrophy, or progression of the zone of atrophy during the follow-up from 2001 to 2006. Conclusions: Hyperopia, short interscleral spur distance, and small optic disc size were, beside older age, the main factors associated with incident early AMD. This may point to a small globe size, potentially in relation to a firmly attached vitreous, playing a role in early incident AMD. Financial Disclosure(s): The authors have no proprietary or commercial interest in any of the materials discussed in this article.
Gesehen am 21.07.2020